Role of immunoproteasomes and thymoproteasomes in health and disease. Issue 6 (3rd March 2021) - Kasahara, Masanori
Abstract : The proteasome is a multisubunit protease that degrades intracellular proteins into small peptides. Besides playing a pivotal role in many cellular processes indispensable for survival, it is involved in the production of peptides presented by major histocompatibility complex class I molecules. In addition to the standard proteasome shared in all eukaryotes, jawed vertebrates have two specialized forms of proteasome known as immunoproteasomes and thymoproteasomes. The immunoproteasome, which contains cytokine‐inducible catalytic subunits with distinct cleavage specificities, produces peptides presented by class I molecules more efficiently than the standard proteasome. The thymoproteasome, which contains a unique catalytic subunit β5t, is a tissue‐specific proteasome expressed exclusively in cortical thymic epithelial cells. It plays a critical role in CD8 + cytotoxic T cell development via positive selection. This review provides a brief overview on the structure and function of these specialized forms of proteasome and their involvement in human disease.